ANALISIS KONTRIBUSI PENERIMAAN PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KOTA MALANG - Hastuti, Poppy Indri; Sulistyawati, Yayuk; Indu, Yasinta Yansi (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2023)
This analysis tries to calculate the additional income provided by restaurant levies on the Unique Income of Malang City Province between 2018 and 2022. Graphic quantitative data is the type of research used to conduct this research. The investigation findings support the theory that income from the Malang City Restaurant Tax Revenue Contribution levy for 2018–2022 varies based on annual salary; especially in 2018 it was 15%, in 2019 it increased to 18%, in 2020 it decreased to 17%, in 2021 it became 15%, and in 2022 there was a very large increase reaching 22%. Therefore, the average annual income from restaurant levies from the Malang City Territorial Unique Pay is 17.4%, which can be assumed to be relatively or moderate.